Reference broadcast synchronization-based prevention to DoS attacks in VANET - Verma, K. (Institute of Electrical and Electronics Engineers Inc., 2014)
Vehicular Ad-hoc Networks (VANET) has suffered from many risks in the past, like security privilege and mode of authentication by many attackers/hackers because they were trying to disturb the network and break communication services for their personal interest. The series of attacks that have broken the secured communication are network jammer, source sink attackand these attacks are called as denial of service (DoS) attacks. A novel model for prevention of DoS attacks in VANET is proposed and named as RBS protocol. The proposed model is based on the master chock filter concept for filtration of packets during busy traffic and other attacks. The protocol was also evaluated by the other two methods, which are blocking the source IP originator by the DoS attacks and checking the prevention of TCP/UDP flooding and IP sniffing attacks. The evaluation of the protocol was based on the mobility node's interaction and utilization of bandwidth. The experimental results were performed on the highway transportation condition. The RBS protocol results showed that the packet delivery ratio, throughput, time delayhas improved as compared to IP-trackback protocol. Â© 2014 IEEE.